In AI we trust? Citizen perceptions of AI in government decision making. Issue 2 (25th November 2021) - Ingrams, Alex; Kaufmann, Wesley; Jacobs, Daan
Abstract: Using a survey experiment on the topic of tax auditing, we investigate artificial intelligence (AI) use in government decision making through the lenses of citizen red tape and trust. We find that individuals consider an AI‐led decision to be lower in red tape and trustworthiness than a decision by a human. We also find that highly complex tasks produce decisions with higher levels of perceived red tape, but that this effect does not vary according to whether the task is AI‐ or human‐led. We argue that researchers and practitioners give more attention to the balance of instrumental and value‐based qualities in the design and implementation of AI applications. Abstract : 通过使用一项关于税务审计主题的调查实验，我们透过公民官僚程序和信任的视角，研究了政府决策中人工智能（AI）的使用。我们发现，个体认为基于AI的决策与人工决策相比，前者的官僚程序更少，可信度更低。我们还发现，高度复杂的任务所产生的决策具备更高程度的感知官僚程序，并且无论任务由AI完成或由人工完成，这一效果都不变。我们主张，研究者和从业人员应更多地关注AI应用程序设计和执行过程中工具性质和基于价值的性质之间的平衡。 Abstract : Utilizamos un experimento de encuesta sobre el tema de la auditoría fiscal para investigar el uso de la inteligencia artificial en la toma de decisiones del gobierno a través de los lentes de la burocracia y la confianza de los ciudadanos. Descubrimos que las personas consideran que una decisión impulsada por la inteligencia artificial tiene menos trámites burocráticos y confiabilidad que una decisión de un ser humano. También encontramos que las tareas muy complejas producen decisiones con niveles más altos de burocracia percibida, pero que este efecto no varía según si la tarea está dirigida por IA o por humanos. Argumentamos que los investigadores y los profesionales prestan más atención al equilibrio de las cualidades instrumentales y basadas en valores en el diseño y la implementación de aplicaciones de IA.